Structure and properties of a personalized bio-fixed implant prepared with selective laser melting. Issue 13 (3rd October 2019) - Zhang, Guoqing; Li, Junxin; Li, Jin; Zhou, Xiaoyu; Wang, Anmin
Abstract: Personalized bio-fixed implants require good modeling efficiency, matching, and stress distribution for optimal function. We performed three-dimensional reconstruction of the tibial implant using reverse and positive methods, performed finite element analysis, and then used the optimized model structure and the optimal node arrangement of the finite element method to design a biomechanical tibia implant. Next, we used selective laser melting equipment for direct manufacturing and then determined the mechanical properties of the completed implant unit structure. The results indicated that the finite element method allows good modeling, the strain performance is equivalent to that of material produced using the traditional modeling method, and the resulting product has a more even stress distribution. The porous structure of the material formed by SLM showed a good forming effect within 3 mm of the pillar, had less powder adhesive on the surface, and lacked obvious dross, suggesting the utility of this method for preparation of personalized bio-fixed implants.